Changes in the morphology and ultrastructure of the Dufour's gland during the life cycle of the bumble bee queen, Bombus terrestris L-(Hymenoptera : Bombini) - Abdalla, Fábio Camargo [UNESP]; Velthuis, H.; Cruz-Landim, Carminda da [UNESP]; Duchateau, M. J. (Brill Academic Publishers, 1999)
The Dufour's gland is found closely associated with the sting apparatus of all female hymenopterans, playing multiple roles among bees. In some species of Bombus the gland may be involved in production of nestmate recognition pheromones, but in B. terrestris its function is not certain yet. The morphology of the :Dufour's gland of B. terrestris queens and the ultrastructural features of its cells were studied in different ages and behavioural stages using routine transmission electron microscopy. Measurements of the length and the diameter of the gland in the same conditions were also made. The Dufour's gland of the queen increases significantly in size (both in length and in diameter) with age and reproductive activity the ultrastructural features of the gland show electrondense material that comes from the haemolymph. This material is also present in the intercellular spaces, and is conducted to the subcuticular space, to be released directly into the glandular lumen. Hence at least part of the secretion is probably taken up directly from the haemolymph. The ultrastructural features indicate a more active phase of the gland corresponding to the period of egg-laying of the queen, and a decrease in activity when the queen is in hibernation as well as after the competition point. In conclusion, the gland is probably involved in reproduction, more specifically, in the marking off eggs.
Keywords: Dufour's gland; bumble bee; queen; Hymenoptera; morphology; ultrastructure